SELENBP1 overexpression in the prefrontal cortex underlies negative symptoms of schizophrenia - Kim, Soojin; Kim, Seong-Wook; Bui, Mai Anh Thi; Kim, Yeji; Kim, Minsoo; Park, Jung-Cheol; Kim, Nam-Heon; Pyeon, Gyeong Hee; Jo, Yong Sang; Jang, Jaewon; Koh, Hae-Young; Jeong, Chae-Hong; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
The selenium-binding protein 1 (SELENBP1) has been reported to be up-regulated in the prefrontal cortex (PFC) of schizophrenia patients in postmortem reports. However, no causative link between SELENBP1 and schizophrenia has yet been established. Here, we provide evidence linking the upregulation of SELENBP1 in the PFC of mice with the negative symptoms of schizophrenia. We verified the levels of transcripts in postmortem PFC brain tissues from patients with schizophrenia and matched healthy controls. We also generated transgenic mice expressing human SELENBP1 (hSELENBP1 Tg) and examined their neuropathological features, intrinsic firing properties of PFC 2/3-layer pyramidal neurons, and frontal cortex (FC) electroencephalographic (EEG) responses to auditory stimuli. Schizophrenia-like behaviors in hSELENBP1 Tg mice and mice expressing in the FC were assessed. transcript levels were higher in the brains of patients with schizophrenia than in those of matched healthy controls. The hSELENBP1 Tg mice displayed negative endophenotype behaviors, including heterotopias- and ectopias-like anatomical deformities in upper-layer cortical neurons and social withdrawal, deficits in nesting, and anhedonia-like behavior. Additionally, hSELENBP1 Tg mice exhibited reduced excitabilities of PFC 2/3-layer pyramidal neurons and abnormalities in EEG biomarkers observed in schizophrenia. Furthermore, mice overexpressing in FC showed deficits in sociability. These results suggest that upregulation of SELENBP1 in the PFC causes asociality, a negative symptom of schizophrenia.